The Educational Status of Turks in Minority Schools: A Qualitative Exploration in Western Thrace - Tösten, Rasim; Han, Bünyamin; Göçken, Burak Erdem (Dinamika Ilmu, 2025)
The main purpose of this research is to address the educational status of Turks living in Western Thrace in minority schools. After the establishment of the Republic of Türkiye, the Thrace region was divided into East and West, with Western Thrace now covering parts of Greece and Bulgaria. Around 150,000 Turks live in this region, facing social challenges, particularly in education. This research examines the problems experienced by Turks in minority education, the struggles in the process and its effects. The research is qualitative and designed with a phenomenological pattern. The study group comprises 13 participants selected through the maximum sampling method. The selection criteria for participants included: completion of primary and secondary education in minority schools in Greece, pursuit of higher education in Türkiye, and experience in teaching or working in a Greek minority school. Data were collected through a semi-structured interview form, with interviews recorded and analyzed using content analysis. The prominent conclusions are as follows: There are cultural problems in the education of Turkish minorities in Greece and there are legal obstacles to solution; there has been a struggle on this issue for years, there have been periodic improvements, but the fundamental problems still continue; it has been seen that many people, such as Dr. Sadık Ahmet, pioneered civil initiatives and that the initiatives had positive and negative effects. In conclusion, this research highlights the ongoing challenges faced by the Turkish minority in Western Thrace regarding their education. Despite periodic improvements and civil initiatives, fundamental problems persist due to cultural barriers and legal restrictions. The findings emphasize the need for continued efforts to address these issues and propose solutions to improve minority education in Greece. It is recommended that legal and educational reforms be implemented to address the challenges faced by the Turkish minority in Western Thrace, ensuring equal and improved access to quality education.